Usuários de crack na contemporaneidade : entre urubus diplomados e o canto dos sabiás - Trindade, Jayane Pinheiro (2015)
From a genealogical perspective, this theoretical and conceptual work, addresses the current field of mental health, in particular, alcohol and other drugs. The current context sometimes is dominated by criminalizing and medicalized perspectives with regard to the use and care for drug users. Therefore, we have claimed to question such reductionist practices in the light of power analyzes carried out by Michel Foucault‟s genealogical perspective, focusing in particular, the strategic function of Compulsory Admission, used today for crack users in the streets, like the cracolândias in São Paulo and Rio de Janeiro cities.This hospitalization provided by law, is an action taken in individual and specific cases, backed by court order, indicated when the person is endangering his own life or that of third parties and has already exhausted all other intervention resources. The methodology used was the genealogy, in order to understand some power games built throughout history and analyze how these still operate and are updated in the contemporary. Michel Foucault‟s genealogy (Power-Know) analyzes the onset of knowledge, which takes place from conditions of external possibilities for own knowledge, that is, lie them as elements of a strategic nature essentially device. Foucault points out the existence of a network of articulated micro powers to the State and that permeate the entire social structure. For that we used some research and Michel Foucault´s reflections on the disciplinary power and biopower. Thus, from these reflections on trying to understand other possibilities of expansion of the practice regarding crack users in the streets.